Growth retardation in artistic compared with rhythmic elite female gymnasts - Georgopoulos, N. A.; Markou, K. B.; Theodoropoulou, A.; Benardot, D.; Leglise, M.; Vagenakis, A. G. (The Journal of Clinical Endocrinology & Metabolism, 2002)
We studied 129 female rhythmic gymnasts (RG) and 142 female artistic gymnasts (AG) who participated in the 1999 Gymnastics World Championship for RG in Osaka, Japan, and the 1999 and 2001 Gymnastics World Championships for AG in Tianjin, China (n = 48), and Ghent, Belgium (n = 94), respectively. RG were taller than average, with a mean height SD score above the 50th percentile, whereas AG were relatively short, with a mean height SD score below the 50th percentile. Both RG and AG followed their respective reported target height SD score, which was above the 50th percentile for the RG and below the 50th percentile for the AG. The RG followed a growth pattern that was higher than their reported target height, whereas AG exhibited a negative growth pattern. RG and AG weighed less than the population mean, with the mean weight for age below the 50th percentile for both groups. RG were taller than AG (t = 17.15; P < 0.001), with a higher reported target height SD score (t = 6.44; P < 0.001), a greater height-reported target height (t = 2.74; P < 0.001), and a lower mean body fat (t = -11.83; P < 0.001) and body mass index (t = -10.73; P < 0.001) than AG. AG started their training at an earlier age than RG (t = 4.13; P < 0.001). Using multiple regression analysis, actual height SD score was independently influenced positively by weight SD score for both RG (b = 0.421; t = 4.317; P < 0.001) and AG (b = 1.404; t = 16.514; P = <0.001), and by reported target height only for RG (b = 0.299; t = 3.139; P = 0.002), and negatively by body mass index only for AG (b = -0.80; t = -9.88; P < 0.001). In conclusion, in elite female AG, a deterioration of growth potential was observed, whereas in RG the genetic predisposition to growth was preserved. Source: The Journal of Clinical Endocrinology & Metabolism Vol. 87, No. 7 3169-3173